2018
DOI: 10.2174/1381612823666170822101606
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Potential Mechanisms of Chinese Herbal Medicine on Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is one of the most common functional bowel disorders (FBD), which is characterized by recurrent abdominal pain, abdominal bloating/distention associated with defecation or changed bowel habits. Currently, there is no evidence of obvious anatomic or physiologic abnormalities on the routine diagnostic examinations. There are multiple pathological factors involved in IBS responsible for its heterogeneous nature, although the exact etiology and pathology of IBS are not well known and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…However, Chinese herbal therapies have been used to treat diarrhea for thousands years in eastern Asia ( Chen et al, 2015 ). Generally, Chinese herbal medicine (CHM) including several herbals from traditional Chinese herbal formulae (CHF), which containing many different ingredients may act on multiple sites/pathways with potential synergistic effects and chemical reactions ( Bi et al, 2017 ). Nowadays, it has been shown that CHM are effective in relieving symptoms among patients and rats with IBS-D ( Mao et al, 2017 ; Fan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Chinese herbal therapies have been used to treat diarrhea for thousands years in eastern Asia ( Chen et al, 2015 ). Generally, Chinese herbal medicine (CHM) including several herbals from traditional Chinese herbal formulae (CHF), which containing many different ingredients may act on multiple sites/pathways with potential synergistic effects and chemical reactions ( Bi et al, 2017 ). Nowadays, it has been shown that CHM are effective in relieving symptoms among patients and rats with IBS-D ( Mao et al, 2017 ; Fan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the large number of alternative treatment options, Chinese herbal medicine (CHM) is one of the most popular 6 . Accumulating evidence shows that CHM has benefit in relieving IBS symptoms and improving quality of life 7–11 . In the trials and meta‐analyses that examined the effect of CHM on IBS, most of them compared CHM with placebo; few of them compared CHM directly with conventional treatments 8,10,12‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Accumulating evidence shows that CHM has benefit in relieving IBS symptoms and improving quality of life. [7][8][9][10][11] In the trials and meta-analyses that examined the effect of CHM on IBS, most of them compared CHM with placebo; few of them compared CHM directly with conventional treatments. 8,10,[12][13][14][15][16] Two recent trials comparing CHM with pinaverium showed that CHM was as effective as pinaverium 7,17 ; one trial showed that CHM was equivalent to pinaverium in relieving abdominal pain, 7 another trial showed that CHM was superior over pinaverium in relieving gastrointestinal symptoms.…”
mentioning
confidence: 99%
“…[ 5 ] HMs contain various ingredients, and these can act on multiple targets with potential synergistic effects; HMs that have been used to treat IBS-related symptoms for centuries with satisfactory effects will be the optimal choice. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%